Caracterização do perfil profissional e modos de atuação do orientador educacional na rede pública de ensino de Sobral-CE - Barbosa, Hiara da Silva Santos (2022)
The research presents the characterization of the professional profile and modes of action of the Educational Advisor (O.E) in the public school system of Sobral-CE. A situational diagnosis was carried out through the application of forms and virtual conversation wheels, as well as a bibliographic survey regarding the implementation of the position in the Municipality. Eleven O.E who work in schools of early and/or final years of elementary school participated in the study, in the territories of the urban and rural areas of the City. Among the main results are: in relation to the professional profile, the study indicates that educational advisors have an academic background in Psychology and, in the majority, qualifications in the educational area, followed by the health, legal and organizational areas. In relation to its way of acting, we found a variety of activities that include pedagogical attributions linked to the implementation of socio-emotional competences (CSE), professional attributions aimed at the development of interpersonal relationships, conflict resolution methodologies and training actions, being the target audience, primarily students and teachers.